Entirely Robotic-assisted Microsurgical Anastomoses in Autologous Breast Reconstruction - Arkudas, Andreas; Horch, Raymund E.; Kümmerl, Luca (Plastic and Reconstructive Surgery Global Open, 2026)
Summary: – Robot-assisted microsurgical arterial anastomosis has become increasingly common in autologous breast reconstruction in recent years. The aim of this study was to perform both arterial and venous microsurgical anastomoses using the da Vinci robotic system in autologous breast reconstruction. Preliminary tests were conducted to determine the optimal instruments, handling techniques, and procedural steps for robot-assisted microsurgical anastomosis of both the artery and the vein. The patient was a 39-year-old woman who underwent a skin-sparing mastectomy for breast cancer followed by expander placement. Robot-assisted microsurgical anastomosis of a muscle-sparing type II transverse rectus abdominis myocutaneous flap was successfully performed using the da Vinci Xi robot without complications. A 3.0-mm coupler system was used for the venous anastomosis, and 8-0 sutures were used for the arterial anastomosis. Anastomotic patency was verified intraoperatively using the da Vinci Firefly indocyanine green function. The intraoperative and postoperative courses were uneventful, with no complications observed. In addition to its established applications in autologous breast reconstruction, the da Vinci robotic system is also suitable for performing microsurgical anastomoses. We were able to show that both arterial and venous anastomoses in autologous breast reconstruction can be performed safely using the da Vinci robot. Compared with other microsurgical robotic platforms, key advantages of the da Vinci system include its integrated camera, 4-port configuration, and integrated indocyanine green function.
CRIS-Team Scopus Importer:2026-06-26